Losing half the crown hardly affects the stem growth of a xeric southern beech population - Reiter, Ernesto J.; Weigel, Robert; Leuschner, Christoph (Scientific reports, 2025)
Globally, forest ecosystems face increasing climate warming-driven stress. Crown dieback is commonly used as an indicator of declining tree vitality and is closely related to reduced stem radial growth rates. In a xeric northern Patagonian Nothofagus pumilio population, in which the majority of trees possess damaged crowns, we explored the relationship between percent crown damage and growth trends (basal area increment, BAI), interannual growth variability, and the climate sensitivity of growth. The majority of trees show stable BAI since about 1940 despite 5 to > 50% crown damage, which ranges from dieback of small branches to the presence of decades-old snagged branches. A minority of trees with more severe crown damage (> 50 to 95%) show continued growth decline during the last 80 years, but have not yet died. Crown damage was the best predictor of the BAI trend which turned negative at about 50% damage. Stronger damaged trees showed a higher growth sensitivity to summer heat and drought. Thus, the health of this population is apparently not threatened by crown damage up to 50%. Rather, trees might profit from the reduced foliage area, allowing them to stabilize their water relations and maintain stable but fairly slow growth in a drying climate.